Security Assessment of Low-Resource Edge Devices for IoT Systems - Shapsough, Shams Eddeen Yousef (2020)
A Master of Science thesis in Computer Engineering by Shams Eddeen Yousef Shapsough entitled, “Security Assessment of Low-Resource Edge Devices for Iot Systems”, submitted in April 2020. Thesis advisors are Dr. Imran Zualkeman and Dr. Fadi Aloul. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).